What Drive Islamic Financial Inclusion in Banda Aceh City? - Putri Ghina Marla; Said Musnadi; M. Shabri Abd. Majid (AL-MUZARA'AH, 2024)
This empirical study explores the role of Islamic financial literacy in strengthening Islamic financial inclusion through financial technology, digital finance, and social capital. Analyzing 385 respondents using Structural Equation Modeling (SEM), the findings reveal significant direct effects of Islamic financial literacy on financial technology, digital finance, and social capital. Additionally, these factors collectively impact Islamic financial inclusion. Mediating effects demonstrate that financial technology, digital finance, and social capital mediate the influence of Islamic financial literacy on Islamic financial inclusion. Implications include the prioritization of Islamic finance education to enhance public understanding and the need for collaborative efforts to establish Shariah-compliant financial technology infrastructure. Fostering social capital is crucial, reducing resistance to change and increasing participation in Islamic financial services. The study underscores an integrated approach, combining education, technological innovation, and social capital development for robust Islamic financial inclusion, promoting sustainable economic growth.